Liver fibrosis of hepatitis C virus infection in routine hemodialysis patients in Indonesia (Medical Journal of Indonesia, 2019)
BACKGROUND The risk of hepatitis C virus (HCV) infection is increasing in patients under routine hemodialysis, but only some patients progress to liver fibrosis. This study was aimed to identify the prevalence of significant liver fibrosis in routine hemodialysis patients with hepatitis C infection as well as factors associated with liver fibrosis. METHODS This cross-sectional study was conducted in three tertiary general hospitals (Cipto Mangunkusumo Hospital, Persahabatan Hospital, and Fatmawati Hospital) in Jakarta, Indonesia, among hemodialysis patients infected with HCV. Total sampling was used from May to September 2017 in hemodialysis unit of all hospitals. Sex, age, time at first diagnosis of HCV, duration of HCV infection, duration of hemodialysis, AST level, hepatitis B virus coinfection and diabetes mellitus were analyzed in association with significant liver fibrosis. Liver fibrosis was assessed using transient elastography and considered significant if the value was ≥7.1 kPa. Chi-square, Mann–Whitney U, and Fisher's exact tests were used. Risk model was analyzed with logistic regression. RESULTS Of the 133 hemodialysis patients infected with HCV, 71.4% of the subjects had significant liver fibrosis. In the risk model, male gender (odds ratio [OR] = 3.92; 95% confidence interval [CI] = 1.74–8.84; p < 0.001) and diabetes mellitus (DM) (OR = 2.85; 95% CI = 1.03–7.88; p = 0.043) were associated with significant liver fibrosis. CONCLUSIONS The prevalence of significant liver fibrosis in routine hemodialysis patients with hepatitis C infection was high. Male and DM were associated with significant liver fibrosis.